H-Ferritin nanoparticle-mediated delivery of antibodies across a BBB in vitro model for treatment of brain malignancies. (5th February 2021) - Rizzuto, Maria Antonietta; Dal Magro, Roberta; Barbieri, Linda; Pandolfi, Laura; Sguazzini-Viscontini, Anna; Truffi, Marta; Salvioni, Lucia; Corsi, Fabio; Colombo, Miriam; Re, Francesca; Prosperi, Davide
Abstract : H-ferritin nanoconjugates of CTX and TZ are developed as carriers across the BBB to allow immunotherapy of primary glioblastoma and HER2+ breast cancer brain metastases. The reliability of the strategy is demonstrated using a transwell barrier model. Abstract : Brain cancers are a group of neoplasms that can be either primary, such as glioblastoma multiforme (GBM), or metastatic, such as the HER2+ breast cancer brain metastasis. The brain represents a sanctuary for cancer cells thanks to the presence of the blood brain barrier (BBB) that controls trafficking of molecules, protecting the brain from toxic substances including drugs. Considering that GBM and HER2+ breast cancer brain metastases are characterized by EGFR and HER2 over-expression respectively, CTX- and TZ-based treatment could be effective. Several studies show that these monoclonal antibodies (mAbs) exert both a cytostatic activity interfering with the transduction pathways of EGFR family and a cytotoxic activity mainly through the immune system activation via the antibody dependent cell-mediated cytotoxicity (ADCC). Since the major limitation to therapeutic mAbs application is the presence of the BBB, here we use a recombinant form of human apoferritin (HFn) as a nanovector to promote the delivery of mAbs to the brain for the activation of the ADCC response. Using a transwell model of the BBB we proved the crossing ability of HFn-mAb. Cellular uptake of HFn-mAb by human cerebral microvascular endothelial cells (hCMEC/D3) was demonstrated by confocal microscopy. Moreover, after crossing the endothelial monolayer, HFn-conjugated mAbs retain their biological activity against targets, as assessed by MTS and ADCC assays. Our data support the use of HFn as efficient carrier to enhance the BBB crossing of mAbs, without affecting their antitumoral activity.